Analogue modelling of conjugate strike-slip faults - Xiao, Kunze; Tong, Hengmao (Frontiers in Earth Science, 2024)
IntroductionScaled analogue modelling had become a powerful tool used by structural geologists to study the geometries and evolution of faults.MethodsWe had successfully simulated the geometry and progressive evolution of conjugate strike-slip faults in three sets of symmetric models with varying sandpack thicknesses and two sets of asymmetric models with different angles using scaled sandbox model. Three representative phases from all the models were described, and the structural characteristics of the different models were analyzed comparatively.ResultsThe results show that well-defined X-shaped conjugate strikeslip faults developed in both the symmetric and asymmetric basement models, they had the same acute angle, and the direction of these angle bisectors was perpendicular to the extension direction. In addition, the development of conjugate strike-slip faults in the asymmetric basement was regionalized compared to the symmetric basement, where the two sets of faults less intersect in the model, and the regionality and asymmetry became more apparent as the degree of basement asymmetry increased.DiscussionThe Mohr space diagrams indicate that there are variations in the characteristics of the faults due to changes in the stress state of the model at different stages. In the asymmetric model, there are differences in the number of two faults developed and the intersection relationship in different regions due to the asymmetry in the distribution of the maximum principal stresses. Furthermore, we proposed two synoptic models, namely, the symmetric conjugate strike-slip fault system (SCSFS) model and the asymmetric conjugate strike-slip fault system (ACSFS) model, for conjugate strike-slip fault systems based on the results of the different models. The models and experimental results were compared with natural examples of the two sets of strike-slip fault systems in the Tabei uplift in China’s Tarim Basin, which exhibit many strong similarities in their structural geometries. The two synoptic models proposed based on the analogue models may provide useful templates for the seismic interpretation and mechanism of different types of conjugate strike-slip fault systems in nature and for inferring the orientation of the maximum principal stress.